HAK ANAK ANGKAT DALAM MENDAPATKAN WARISAN DITINJAU DARI HUKUM WARIS INDONESIA - Ridwan Arifin Karin Aulia Rahmadhanty Dian Latifiani (Normative Jurnal Ilmiah Hukum, 2018)
This article is an article about the inheritance rights that apply to adopted children in obtaining inheritance from their adoptive parents and to find out an explanation of inheritance of adopted children in Civil Law, Customary Law and Islamic law. The author already knows about inheritance of adopted children and has searched for comparisons between the three laws in the distribution of inheritance in order to know the weaknesses and strengths of each of the laws, namely the disadvantages are that these three laws each have differences regarding views and status for adopted children. and the advantage is that these three laws provide the truth about the adoption of children who have the goal of caring for the child as their child. The mandate and gift of God Almighty is the giving of a child who must be cared for, and given protection, because in a child there is a dignity, dignity and rights as a human being which must be upheld by its existence. Protection of children's rights is part of human rights as stipulated in the 1945 Constitution of the Republic of Indonesia and the United Nations Convention on the Rights of the Child. Law No.23 of 2002 concerning Child Protection which states that States, governments, communities, families and parents have obligations and responsibilities for the implementation of child protection. Child protection has the aim of ensuring children's rights to be able to live, grow, develop based on human dignity and gain protection in order to avoid violence and discrimination in order to make Indonesian children who have good quality, noble character and prosperity. Appointment of children is not found in the Civil Code (Civil Code). The Civil Code only describes the provisions regarding the recognition of children outside of marriage found in Book I Chapter XII, third part. Through increasing community needs regarding adoption and cultural culture, the community has long explained about adoption, so the Dutch East Indies Government made Staatsbald 1917 No.12 which specifically explained the adoption institutions in Chapter II which are often known as adoption.